1991
DOI: 10.1177/106002809102500605
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hypoprothrombinemic Response to Warfarin Secondary to the Warfarin-Nafcillin Interaction

Abstract: Patients who are receiving multiple medications must be screened for significant drug interactions. The specific mechanism of a drug interaction determines whether the patient may experience a subtherapeutic effect or a potentially toxic reaction. Three cases of relative warfarin resistance, possibly related to high-dose nafcillin, are described in this report. Several reports have suggested that penicillinase-resistant penicillins, such as nafcillin and dicloxacillin, exert an important enzyme-inducing effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Previous reports suggested that penicillinase-resistant penicillins can induce cytochrome P450 isoenzymes involved in warfarin metabolism and lead to warfarin-resistance [4,5,6,7,8,9,10,11,12,13]. Cloxacillin-induced changes in warfarin metabolism cannot explain the increased anticoagulation activity in this case.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previous reports suggested that penicillinase-resistant penicillins can induce cytochrome P450 isoenzymes involved in warfarin metabolism and lead to warfarin-resistance [4,5,6,7,8,9,10,11,12,13]. Cloxacillin-induced changes in warfarin metabolism cannot explain the increased anticoagulation activity in this case.…”
Section: Discussionmentioning
confidence: 69%
“…The literature does not provide strong evidence of the clinically significant interaction between warfarin and penicillinase-resistant penicillins. Several reports document warfarin-resistance in patients treated with dicloxacillin, nafcillin, and flucloxacillin [4,5,6,7,8,9,10,11]. This drug-induced warfarin-resistance often develops within 7 days of starting antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Three other case reports documenting a warfarin-nafcillin interaction have described a 2-5-fold increase in warfarin requirements with nafcillin coadministration. [8][9][10] In a review of warfarin induction interactions, induction by nafcillin was usually evident within 1 week, and warfarin requirements returned to baseline doses 1-4 weeks after nafcillin discontinuation. 12 The authors of a review of warfarin drug and food interactions determined that this drug interaction was highly probable.…”
Section: Discussionmentioning
confidence: 99%
“…Authors of case reports also have suggested that nafcillin leads to warfarin resistance due to nonselective enzyme induction. [5][6][7][8][9][10] Although the authors of one report suggested that dicloxacillin also may induce CYP enzymes, 10 this effect has not been reported with oxacillin.…”
Section: Discussionmentioning
confidence: 99%
“…Within the 9 published case reports, a total of 11 patient cases were described including: 4 warfarin-naïve patients at the time nafcillin was initiated (1 of which was a pediatric patient), 4 stable warfarin patients prior to initiation of nafcillin, 2 stable warfarin patients prior to initiation of dicloxacillin, and 1 stable warfarin patient at the time of nafcillin initiation that was changed to dicloxacillin. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In the warfarin-naïve patients, higher initial warfarin doses (5-12 mg/day) were needed initially during nafcillin treatment. The weekly warfarin doses were typically two-to fourfold higher than the doses after discontinuation of nafcillin.…”
Section: Introductionmentioning
confidence: 99%